2001
DOI: 10.1614/0043-1745(2001)049[0177:poclgp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of common lambsquarters growth parameters

Abstract: Research was conducted to characterize the phenology of common lambsquarters growth parameters as influenced by climatic variation among years. Treatments included soybean or corn grown alone, common lambsquarters with soybean or corn, and common lambsquarters grown alone. Common lambsquarters leaf area and plant height phenology differed among years and was variable within treatments. Conversely, crop leaf area and plant height phenology did not differ among years and was less variable within a treatment than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
1
27
0
3
Order By: Relevance
“…Chenopodium album germinated late and was effectively suppressed by the wheat, especially at higher densities in the uniform pattern. In the absence of such suppression, C. album can be taller than wheat (Colquhoun et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Chenopodium album germinated late and was effectively suppressed by the wheat, especially at higher densities in the uniform pattern. In the absence of such suppression, C. album can be taller than wheat (Colquhoun et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Según Colquhoun et al (2001), estos investigadores, al estudiar en cámaras de crecimiento el efecto de la temperatura y del fotoperíodo sobre la longitud de tallos, encontraron que la altura de los mismos se incrementaba con el aumento de la temperatura, siendo 1,55 m y 0,26 m, con fotoperíodos de 16 y 8 horas de luz, respectivamente. En las condiciones de este ensayo, se registraron temperaturas similares a las mencionadas por Huang et al (2001) y Roman et al (1999, que le permitieron alcanzar y superar en altura al cultivo, aunque la emergencia de maleza y cultivo hayan sido simultáneas (Tabla 1).…”
Section: Resultados Y Discusiónunclassified
“…Un índice bajo indica que en la distribución actúan numerosas plantas, que se desarrollan en torno a una planta principal o sobresaliente. El desarrollo de estrategias alternativas, basadas en el conocimiento de la biología y ecología de CHEAL, es necesario, particularmente, en bajas densidades de malezas, lo que es común en sistemas de cultivos (Colquhoun et al, 2001). Los resultados de este ensayo coinciden con lo expresado por Gramid & Stoltenberg (2009) respecto a que esta maleza incrementa su altura, la biomasa de tallos y disminuye la biomasa de hojas cuando crece bajo el canopeo de un cultivo.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…(2003) found similar decreases for A. retroflexus when grown within a maize canopy and Légère and Schreiber (1989) found that A. retroflexus biomass was reduced in the presence of a soyabean canopy. Colquhoun et al. (2001) found that C. album height were similar with (∼40–110 cm at 700 growing degree days) and without (∼70–100 cm at 700 growing degree days) a soyabean crop, although the differences among years were greater in the treatments where soyabean was present.…”
Section: Weed Characteristicsmentioning
confidence: 93%